2019
DOI: 10.2477/jccj.2019-0046
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Thermodynamics Database Construction to Search for Novel Ionic Liquids with Gas Selectivity

Abstract: Ionic liquids (ILs) are non-volatile and highly stable solvents, which consist of organic/inorganic cations and anions. ILs are attractive since they can be utilized as gas-separating materials. Using a conductor-like screening model for realistic solvation (COSMO-RS) method, in this study, Henry's law constants of 15 gases (HCN,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Via the preparation of the chemistry data set used in content 3, students can also comprehend the background of quantum chemistry. The experimental data and the theory of the method were derived from refs ,− .…”
Section: Development Of Course Contentsmentioning
confidence: 99%
“…Via the preparation of the chemistry data set used in content 3, students can also comprehend the background of quantum chemistry. The experimental data and the theory of the method were derived from refs ,− .…”
Section: Development Of Course Contentsmentioning
confidence: 99%
“…We previously used ILs to develop a process for effectively separating CO 2 from gas mixtures by physisorption. 17 In a previous study, Kuroki et al used a conductor-like screening model for the real solvents (COSMO-RS) method and machine learning to predict CO 2 Henry's law constants for more than tens of thousands of ILs 18,19 and reported that t r i h e x y l ( t e t r a d e c y l ) p h o s p h o n i u m b i s -(trifluoromethanesulfonyl)amide ([P 66614 ][TFSA]), trihexyl-(tetradecyl)phosphonium perfluorooctanesulfonate ([P 66614 ]-[PFOS]), and trihexyl(tetradecyl)phosphonium hexafluorophosphate ([P 66614 ][PF 6 ]) as ILs exhibited superior CO 2 absorption. 20 According to Henry's law constants calculated by machine learning, the CO 2 solubilities for PFOS − and PF 6 − were predicted to be similar to or better than TFSA − .…”
Section: Introductionmentioning
confidence: 99%
“…According to Henry’s law constants calculated by machine learning, the CO 2 solubilities for PFOS – and PF 6 – were predicted to be similar to or better than TFSA – . However, using a magnetic suspension balance to measure the CO 2 solubility, we succeeded in observing that PFOS – was better than TFSA – . Therefore, accurate experimental measurements supervised by theoretical fast screening are important.…”
Section: Introductionmentioning
confidence: 99%
“…13−20 Recently, we proposed a method combining COSMO-RS and machine learning technique to quickly predict gas selectivity for pure ILs with high accuracy. 21 In this study, we performed comprehensive COSMO-RS calculations for mixed ILs, which are 1:1 mixtures of [cation][anion A ] and [cation][anion B ], to predict changes in the Henry's law constants of CO 2 upon mixing. Using quantum chemical insight, we propose IL mixing conditions for obtaining better CO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%
“…To theoretically predict the properties of ILs prior to experiments, it is essential to apply ab initio molecular theory. In this study, we focused on the conductor-like screening model for realistic solvation (COSMO-RS), which is a statistical thermodynamic calculation method based on quantum chemical calculations, proposed by Klamt et al The COSMO-RS method has been widely used in the field of chemical engineering because it is a powerful tool to evaluate the physicochemical and thermodynamic properties of functional liquids including ILs. Recently, we proposed a method combining COSMO-RS and machine learning technique to quickly predict gas selectivity for pure ILs with high accuracy . In this study, we performed comprehensive COSMO-RS calculations for mixed ILs, which are 1:1 mixtures of [cation]­[anion A ] and [cation]­[anion B ], to predict changes in the Henry’s law constants of CO 2 upon mixing.…”
Section: Introductionmentioning
confidence: 99%